MoO3 on zeolites MCM-22, MCM-56 and 2D-MFI as catalysts for 1-octene metathesis - Balcar, Hynek; Kubů, Martin; Žilková, Naděžda; Shamzhy, Mariya (Beilstein journal of organic chemistry, 2018)
Highly active olefin metathesis catalysts were prepared by thermal spreading MoO3 and/or MoO2(acac)2 on MWW zeolites (MCM-22, delaminated MCM-56) and on two-dimensional MFI (all in NH4 + form). The catalysts' activities were tested in the metathesis of neat 1-octene (as an example of a longer chain olefin) at 40 °C. Catalysts with 6 wt % or 5 wt % of Mo were used. The acidic character of the supports had an important effect on both the catalyst activity and selectivity. The catalyst activity increases in the order 6MoO3/HZSM-5(25) (Si/Al = 25) << 6MoO2(acac)2/MCM-22(70) < 6MoO3/2D-MFI(26) < 6MoO3/MCM-56(13) < 6MoO3/MCM-22(28) reflecting both the enhancing effect of the supports' acidity and accessibility of the catalytic species on the surface. On the other hand the supports' acidity decreases the selectivity to the main metathesis product C14 due to an acid-catalyzed double bond isomerization (followed by cross metathesis) and oligomerization. 6MoO3/2D-MFI(26) with a lower concentration of the acidic centres resulting in catalysts of moderate activity but with the highest selectivity.
Keywords: zeolites; metathesis; thermal spreading; molybdenum oxide; 1-octene